Outgassing rate measurements with the difference method in the framework of EMRP IND12. (December 2015) - Hauer, V.; Battes, K.; Flämmich, M.; Ierardi, V.; Jousten, K.; Šetina, J.
Abstract: A new outgassing rate facility applying the difference method was established at KIT. This system was validated within the framework of Joint Research Project IND 12 of the European metrology Research programme by several outgassing reference probes. These served as transfer standards for comparison with three other outgassing rate systems available in the project. Two of the probes were newly developed reference devices and exhibit a known, constant outgassing rate of water. Further two probes were also newly developed outgassing reference devices which emit mixtures of gases. Additionally another probe was an elastomer which was loaded with a known gas mixture. The last probe was a commercially available plastic material whose outgassing shows a large spectrum of gases. The other outgassing rate facilities applied the in-situ calibration of quadrupole mass spectrometers by a primary method, the continuous expansion method (Physikalisch-Technische Bundesanstalt) and the known gas quantity method (Institute of Metals and Technology) or the throughput method (VACOM company). The comparison of the results shows a satisfactory agreement between the measurements. Highlights: Round robin experiment including four facilities for outgassing rate measurements. Four candidate reference probes with a known, constant outgassing rate of water or gas mixtures. One probe was loaded with a known gas mixture. One probe was a commercially available material whose outgassing shows a large spectrum of gases. Comparison of the results shows a satisfactory agreement between the measurements.